A Significantly High Abundance of “Candidatus Liberibacter asiaticus” in Citrus Fruit Pith: in planta Transcriptome and Anatomical Analyses - Fang, Fang; Guo, Hengyu; Zhao, Anmin; Li, Tao; Liao, Huihong; Deng, Xiaoling; Xu, Meirong; Zheng, Zheng (Frontiers in Microbiology, 2021)
Huanglongbing, a highly destructive disease of citrus, is associated with the nonculturable phloem-limited α-proteobacterium ‘Candidatus Liberibacter asiaticus’ (CLas). The distribution patterns of CLas in infected plant are variable and not consistent, which make the CLas detection and characterization more challenging. Here, we performed a systemic analysis of CLas distribution in citrus branches and fruits of 14 cultivars. A significantly high concentration of CLas was detected in fruit pith (dorsal vascular bundle) of 14 citrus cultivars collected at fruit maturity season. A two-year monitoring assay of CLas population in citrus branches of ‘Shatangju’ mandarin (Citrus reticulata Blanco ‘Shatangju’) revealed that CLas population already exhibited a high level even before the appearance of visual symptoms in the fruit rind. Quantitative analyses of CLas in a serial 1.5-cm segments of fruit piths showed the CLas was unevenly distributed within fruit pith and tended to colonize in the middle or distal (stylar end) regions of pith. The use of CLas-abundant fruit pith for dual RNA-Seq generated a higher resolution CLas transcriptome data compared to the leaf samples. CLas genes involved in transport system, flagellar assembly, lipopolysaccharide biosynthesis, virulence, stress response and cell surface structure, as well as host genes involved in biosynthesis of antimicrobial-associated secondary metabolites, were up-regulated in leaf midribs compared with fruit pith. In addition, CLas infection caused the severe collapse in phloem and callose deposition in the plasmodesmata of fruit pith. The ability of fruit pith to support multiplication of CLas to high levels makes it an ideal host tissue for morphological studies and in-planta transcriptome analyses of CLas-host interactions.